GIS as a decision support tool for landfill site - Ak Mohd Rafiq Ak Matusin; Fiffy Hanisdah Saikim; Norazah Mohd Suki; Mahadi Menakbar M. Dawood (PeerJ, 2015)
GeographicallnfomuJtion System (GIS) can aid decision makers to make a righl and reliable choice 10 locale a specific site such as selecting the best possible site for sanitary landfills. The analytical techniques presented in this research will serve as a vaJlUJble and useful tool for professionals namely enginurs. lown planners and other panies involved to properly zone an area for a specific lise. A detailed crirerion based on Landfills Siting Guidelines prepared by the Malaysian Depanment of Environment was used as a guide to tUtermine the ~st location. These crituia were then analysed using Constraint Mopping Technique to evaluate and sed potential locations of sanitary landfills. Aftu Ihe potential siles had bun found in several locations. appropriale ranking techniques by means of GIS were then applied to help decide the ~st choices. This research involved the District of Sandakan in Sabah as the study area and in the study six Potential Search Areas were identified for sanitary landfill sires.